As I lay dying [videorecording (DVD)] - Franco, James, 1978-; Rager, Matt; McBride, Danny, 1976-; Nelson, Tim Blake; Marshall-Green, Logan, 1976-; O'Reilly, Ahna, 1985-; Faulkner, William, 1897-1962 (Millennium Entertainment, 2013)
Tells the story of the death of Addie Bundren and her family's mission to honor her desire to be buried in the nearby town of Jefferson.